2016
DOI: 10.14238/pi56.1.2016.05
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive breastfeeding rate and factors associated with infant feeding practices in Indonesia

Abstract: Background Breast milk is the ideal food for infants. According

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
2
0
1
Order By: Relevance
“…The rates of exclusive breastfeeding (62.4%) in our study, to our surprise, were higher than we expected from the statistics provided by these study PHCs (14.8 to 25.0%) and were higher than the national estimates (37.3%) in Indonesia [ 4 ]. Nevertheless, the result of this study was consistent with the rates of exclusive breastfeeding (63.3%, 60%) reported in two recent studies conducted in Yogyakarta regions [ 24 , 25 ], in which the definition for exclusive breastfeeding by WHO during the first 6 months postpartum was adopted. The relatively high exclusive breastfeeding rates in Yogyakarta regions might be related to multilevel breastfeeding interventions launched since 2012, including peer breastfeeding support and lactation counseling [ 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…The rates of exclusive breastfeeding (62.4%) in our study, to our surprise, were higher than we expected from the statistics provided by these study PHCs (14.8 to 25.0%) and were higher than the national estimates (37.3%) in Indonesia [ 4 ]. Nevertheless, the result of this study was consistent with the rates of exclusive breastfeeding (63.3%, 60%) reported in two recent studies conducted in Yogyakarta regions [ 24 , 25 ], in which the definition for exclusive breastfeeding by WHO during the first 6 months postpartum was adopted. The relatively high exclusive breastfeeding rates in Yogyakarta regions might be related to multilevel breastfeeding interventions launched since 2012, including peer breastfeeding support and lactation counseling [ 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…It is consistent with studies conducted in; Motta town, Ethiopia 50.1% [ 14 ], Gahanna 64% [ 20 ], Debre Markos, Ethiopia 60.8% [ 29 ], Ecuador 62.8% [ 35 ] and Hawassa, Ethiopia 60.9% [ 16 ]. On the other hand, the result was higher than the studies done in; Indonesia 40% and 46% [ 36 , 37 ] Saudi Arabia 43.9% [ 38 ], Nigeria 33.5% [ 39 ], Papua New Guinea 17% [ 40 ], Democratic Republic Congo 39% [ 41 ], Addis Ababa, Ethiopia 29.3% [ 11 ] and North West Ethiopia 30.7% [ 12 ]. However, the result was lower than studies conducted in; Debre Birhan, Ethiopia 68.6% [ 17 ],Afar, Ethiopia 81.1% [ 19 ], Tigray, Ethiopia70.2% [ 18 ], United States73% [ 28 ] and India 87% [ 42 ].…”
Section: Discussionmentioning
confidence: 76%
“…In the same year the Indonesian ministry of health reported that the EBF rate was 54% nationwide. The current national Indonesian EBF rate of 46.3% [ 34 ] is above the global average rate of EBF (37% across 75 countries), [ 11 ] although it is still below the Indonesian government’s target of >75% [ 35 ]. The higher EBF rate in our study may be due to the families’ engagement in the vaccine clinical trial, providing a higher exposure to health care providers and to the national program that encouraged EBF.…”
Section: Discussionmentioning
confidence: 99%